Discrete modeling of building structures geometric images - Vorontsov, Oleg; Tulupova, Larissa; Vorontsova, Iryna (International Journal of Engineering and Technology, 2018)
For discrete modeling of geometric images, it is possible to use the numerical method of finite differences, the static-geometric method, the mathematical apparatus of numerical sequences. Each of them has certain advantages and disadvantages, which depend on the solution of specific practical problems.This article proposes to use the geometric apparatus of superpositions together with the above-mentioned methods. It allows significantly to improve the efficiency and expanding capacities of the process of geometric images discrete modeling. In particular, it makes it possible to investigate an opportunity of interpolating as parabolic functions as well as other elementary functional dependencies.The purpose of this article is to expand capacities of the classical finite difference method and static-geometric method by using the geometric apparatus of superpositions. It allows using hyperbolic functions as interpolators for the geometric images discrete modeling.The result of this study is the obtained interpolating and extrapolating templates, which allow modeling geometric images of architectural and building constructions in a form of chain lines discrete frames.